The Implementation of Talking Stick Model to Improve Speaking Skills Response for 10th Grade Students of Social Science in MAN Pasir Pengaraian - Arianti, Rita; Wardani, Lia; Marta, Eni (Proceedings of the UR International Conference on Educational Sciences, 2018)
This research is trigerred by low speaking skills of students in delivering responses in learning. This type of research is Classroom Action Research. The research used mixed method asit combines both qualitative and quantitative methods. The purpose of this study is to improve student activity and learning outcomes in learning speaking skills through the application of the Talking Stick model. The results of this study were (1) the quality of student activity in pre-cycle was 60% and it increased to be 64% in cycle I, and increased again in cycle II to be 88%, the quality of student learning activities increased from sufficient quality to very high quality, (2) increased completeness learning outcomes of pre-cycle by 40% with an average class of 61.68 to 68% in cycle I with an average class of 74.04, an increase in the second cycle to 100% with an average class of 84.8. Based on the results of the study it can be concluded that the application of the Talking Stick model can increase the average grade of class X MAN Pasir Pengaraian in speaking skills conveying responses to articles in the mass media.